Terroryzm w obliczu bezpieczeństwa państwa - Dukiewicz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The article focuses on the issue of the threat of terrorism. Terrorism plays a vital role in the environment, gradually becoming a major threat to any conflict affecting the functioning of the state. Experience has shown that in the fight against terrorism, the key to victory is the exchange of intelligence and new techniques and procedures for action. Anti-terrorism methods are continually evolving as a result of new trends and ways in which terrorist activities are carried out.
Keywords: terroryzm; bezpieczeństwo międzynarodowe; zagrożenia bezpieczeństwa; środowisko bezpieczeństwa